Ship Sinking Policy and Socio-Economic Welfare: A Case Study in Sebatik Island, Nunukan District, North Kalimantan Province: Kebijakan Penenggelaman Kapal dan Kesejahteraan Sosial Ekonomi Masyarakat: Studi Kasus pada Masyarakat Kepulauan Sebatik, Kabupaten Nunukan, Provinsi Kalimantan Utara - Maria Agustini Permata Sari; Sujarwoto Sujarwoto (Pusjar SKPP Lembaga Administrasi Negara, 2019)
As an archipelago country, most of Indonesia’s country are located on the sea. Due to this geographic position, illegal fishing becomes an important issue that threatens the country’s maritime security. To solve this issue, the government of Indonesia has implemented